Response to 5‐azacytidine in a patient with TET2‐mutated angioimmunoblastic T‐cell lymphoma and chronic myelomonocytic leukaemia preceded by an EBV‐positive large B‐cell lymphoma. Issue 4 (29th June 2016) - Saillard, Colombe; Guermouche, Helene; Derrieux, Coralie; Bruneau, Julie; Frenzel, Laurent; Couronne, Lucile; Asnafi, Vahid; Macintyre, Elizabeth; Trinquand, Amélie; Lhermitte, Ludovic; Molina, Thierry; Suarez, Felipe; et al.
Abstract: We report the case of a patient with a history of Epstein–Barr virus‐positive large B‐cell lymphoma, who relapsed with an angioimmunoblastic T‐cell lymphoma (AITL) associated with a chronic myelomonocytic leukaemia (CMML). We performed targeted next‐generation sequencing on CMML and AITL DNA, which revealed mutations of TET2, DNMT3A, SRSF2, NRAS and IDH1, thus confirming that the spectrum of AITL mutations share similarities with myeloid disorders. The frequencies of TET2/DNMT3A and SRSF2 variants could support the hypothesis that TET2/DNMT3A mutations occurred in an early progenitor cell, which later progressed to both the AITL and CMML clones. Treatment with 5‐azacytidine led to the complete remission of both diseases. Thus, targeting DNA methylation abnormalities in AITL may be an alternative strategy to chemotherapy. Copyright © 2016 John Wiley & Sons, Ltd.